Perbedaan Manajemen Tenaga Pendidik dan Tenaga Kependidikan di Lembaga Pendidikan Islam - Mamduh, Duduh; Kartika , Ika; Putri A, Cut Cory; Said, Arjun; Wahyud, Didi (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to analyze the differences in management of educators and education personnel in Islamic Educational Institutions. The method used is a qualitative research method with a library research approach. The data in this research is based on facts, reality in the field and not designed by researchers through research. The results of the study indicate that the process of differences in management of educators and education personnel in Islamic Educational Institutions makes it more effective and efficient by paying attention to Islamic teachings. Therefore, in an effort to improve management, it is necessary to increase understanding of Islamic teachings.